APLIKASI SIG UNTUK PEMETAAN POTENSI LOKASI KAWASAN PERDAGANGAN DI KECAMATAN MANTRIJERON YOGYAKARTA - , SAFIRAH FAKHRIA H ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Trade is an economic activity that links between producers and consumers. As distribution activities, trade guarantee circulation, distribution, and supply of goods through the market mechanism. This study aims to determine the potential location of the District Mantrijeron trade area by utilizing the data of Remote Sensing and Geographic Information Systems. Remote Sensing Data used were 2012 Quickbird image. This study uses pengharkatan (scoring) against several influencing parameters including land use, accessibility of positive, negative accessibility, land price, population density, and distance to the field of educational facilities. These parameters are then produced some of the maps to overlay (overlay) to obtain the final result is a Potential Map Location Mantrijeron Trade Area of the District. The results obtained in the form of Potential Location Map Trade Zone District of Mantrijeron are divided into 3 classes: Potential Class I, Class II Potential and Potential Class III. The most dominating classes in District Mantrijeron is a potential Class II, where the positive accessibility is quite good, the land price is low to moderate, with residential land use, schools, shops, and food stalls, making it possible to develop the area into a commercial district.